2021
DOI: 10.1155/2021/9987067
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Lung Cancer Diagnostic Model Based on 6-Gene Methylation Frequency in Blood, Clinical Features, and Serum Tumor Markers

Abstract: Lung cancer has a high mortality rate. Promoting early diagnosis and screening of lung cancer is the most effective way to enhance the survival rate of lung cancer patients. Through computer technology, a comprehensive evaluation of genetic testing results and basic clinical information of lung cancer patients could effectively diagnose early lung cancer and indicate cancer risks. This study retrospectively collected 70 pairs of lung cancer tissue samples and normal human tissue samples. The methylation freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…CDKN2A was silenced in more than 70% of lung squamous cell carcinoma samples. 40 Chunkang et al 21 constructed a lung cancer diagnosis model with 6 genes including CDKN2A (p.16), which can effectively diagnose early lung cancer and indicate cancer risk. In addition, Wei Liu et al 19 reported that CDKN2A indicates a poor prognosis of lung cancer, which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDKN2A was silenced in more than 70% of lung squamous cell carcinoma samples. 40 Chunkang et al 21 constructed a lung cancer diagnosis model with 6 genes including CDKN2A (p.16), which can effectively diagnose early lung cancer and indicate cancer risk. In addition, Wei Liu et al 19 reported that CDKN2A indicates a poor prognosis of lung cancer, which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The area under the curve (AUC) value was calculated to verify the reliability and the accuracy, sensitivity, and specificity were calculated as previously described. 21 …”
Section: Methodsmentioning
confidence: 99%
“…The SVM model was validated calculating the area under the ROC curve and other statistical parameters. Based on these validation data (area under the ROC curve of 0.963 sensitivity of 0.900, specificity of 0.971, and accuracy of 0.936), the scientists proved the validity of the developed method, highlighting the crucial role of ML models as diagnostic tools for an early diagnosis of cancers that can contribute to increasing the survival rate of patients [242].…”
Section: Basic Researchmentioning
confidence: 90%
“…The SVM model was validated by calculating the area under the ROC curve and other statistical parameters. Based on these validation data (area under the ROC curve of 0.963, sensitivity of 0.900, specificity of 0.971, and accuracy of 0.936), the scientists proved the validity of the developed method, highlighting the crucial role of ML models as diagnostic tools for the early diagnosis of cancers that can contribute to increase the survival rate of patients [253].…”
Section: Basic Researchmentioning
confidence: 92%